Cash Flow Statement Analysis on PT Tanaka Citra Gemalang Tangerang Plant 2016-2020 Period - Djodi Hidayat; Kadek Laksmi Chyavani (Politeknik STMI Jakarta, 2024)
Based on PT Tanaka Citra Gemalang cash flow statement, it shows that their cash activities from 2016-2020 have an unstable condition, the difference is very significant, this can cause from Covid-19 pandemic that company has been facing. The purpose of this research is because writer want to know how is the cash flow activities condition and how company can develop their cash flow which in cash flow was included an operation activity, investment activity and funding activity. On this research, writer use cash flow pattern analysis and also horizontal finance analysis. The results from cash flow analysis shows that cash flow have a negative result. With this cash balance which always decreasing on the past three years and company was also having a cash deficit on the past two years, it means that the conclucion of this situation is PT Tanaka Citra Gemalang finance situation is not on well finance situation.